(untitled) (Philosophy and Progress, 2014)
In science theory changes, the old is rejected and the new accepted, the new is considered to be better than the old, this betterment is the essence of scientific progress. But what is the criterion to measure one is better than the other? According to the very traditional view, it is fact which determines the fate of a theory. But since fact itself is not theory free, it cannot be criterion for theory-choice. We find that theory replaces theory. In such a situation, what it is for which one theory can supersede the other. In this essay we have made an investigation about it and we finally find different criteria where in turn one criterion is found to be better than the other to explain scientific change. DOI: http://dx.doi.org/10.3329/pp.v51i1-2.17678